Narrow band imaging characteristics of gastric polypoid lesions: a single-center prospective pilot study. Issue 6 (June 2020) - Esposito, Gianluca; Angeletti, Stefano; Cazzato, Maria; Galli, Gloria; Conti, Laura; Di Giulio, Emilio; Annibale, Bruno; Lahner, Edith
Abstract : Introduction: Gastric polypoid lesions (GPL) are endoscopic findings whose histological nature is difficult to determine with white-light endoscopy. Hyperplastic polyps (HP), type-1 gastric carcinoids (T1-GC) and adenomas are the most frequent GPL needing different management. Narrow-band imaging (NBI) has high accuracy for gastric malignant lesions but few studies assessed whether GPL display specific NBI characteristics. We aimed to investigate the endoscopic NBI appearances of GPL. Materials and methods: During gastroscopies, images of GPL were recorded, and lesions were removed for histological evaluation. Two endoscopists blindly reviewed the digital images and registered the endoscopic NBI appearances on a specific check-list. GPL were categorized in HP, adenomas and T1-GC using histology as gold standard. Results: Overall 52 GPL, observed in 40 patients [F55%; age 63 (36–85) years], were included: 29 (55.8%) HP; 18 (34.6%) T1-GC; 5 (9.6%) adenomas. The median size was seven (2–35) mm. A regular circular mucosal pattern was more frequently observed in HP and T1-GC compared to adenomas ( P < 0.001). T1-GC showed a central erosion in 77.8% ( P < 0.001 versus HP) with a clear demarcation line in 33.3%. Adenomas had tubule-villous mucosal pattern in 80% ( P = 0.01 versus other lesions). Conclusion: NBI analysis of the mucosal pattern seems to be effective to endoscopically discriminate between adenomas and HP while the main characteristic of T1-GC seems to be the presence of a central erosion, sometimes with demarcation line. The endoscopic NBI characterization of GPL may contribute to optimize the management of these lesions.